2008
DOI: 10.1051/gse:2008010
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between Poisson and zero-inflated Poisson regression models with an application to number of black spots in Corriedale sheep

Abstract: -Dark spots in the fleece area are often associated with dark fibres in wool, which limits its competitiveness with other textile fibres. Field data from a sheep experiment in Uruguay revealed an excess number of zeros for dark spots. We compared the performance of four Poisson and zero-inflated Poisson (ZIP) models under four simulation scenarios. All models performed reasonably well under the same scenario for which the data were simulated. The deviance information criterion favoured a Poisson model with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Several studies have shown a considerable improvement in precision by switching from Poisson to the alternative heavier tailed extension like negative binomial, quasi-Poisson, and zero-inflated regression (ZIP) (Ismail and Jemain 2007;Naya et al 2008;Ver Hoef and Boveng 2007). The aforementioned distributions are either compound or mixture of Poisson.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown a considerable improvement in precision by switching from Poisson to the alternative heavier tailed extension like negative binomial, quasi-Poisson, and zero-inflated regression (ZIP) (Ismail and Jemain 2007;Naya et al 2008;Ver Hoef and Boveng 2007). The aforementioned distributions are either compound or mixture of Poisson.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When tests were conducted on the motor claim insurance frequency data, the negative binomial model was found to correct the overdispersion and presented a better fit for the data (David and Jemna 2015). In Naya et al (2008), the authors compared the performance of Poisson and ZIP models under four simulation scenarios to analyze field data and established that the ZIP models gave better estimates than the Poisson models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is well known that the age of the animals affects spot presence (Naya et al 2008;Peñagaricano et al 2011). Nevertheless, and given the paucity of results in this area, we decided, as a first approximation, to sample across ages to concentrate on identifying those candidate genes that are responsible for the development of black spots under white coats independent of the age of the animal.…”
Section: Microarray Analysismentioning
confidence: 99%
“…The choice of regression model and coefficient of correlation is important in theses analysis. In comparison to the Poisson regression model, the ZIP line regression model covers the relation between protein abundance to transcript expression and also ascribes the high percentage of proteins with zero abundance due to technical limitations (102).…”
Section: Proteomicsmentioning
confidence: 99%